Pengaruh Perbedaan Jenis Umpan Terhadap Hasil Tangkapan Ikan Kakap Merah (Lutjanus Gibbus, Forsskal, 1775) Menggunakan Pancing Ulur Di Perairan Wakatobi - La Ode Abdul Muis; Ahmad Mustafa; Romy Ketjulan; Naslina Alimina; Abdullah Abdullah (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2023)
This research aims to determine the effect of different types of bait (squid, mackerel, and scad) on the number and size of red snapper caught using hand line. The study was conducted during February 2022, in Wakatobi Waters, Southeast Sulawesi Province, specifically in Koko Atol, Koromaha Atol, Tuwu-Tuwu Reef, and Kenteolo Reef. This study used experimental fishing method with 6 fishing trips and 25 repetitions on each trip. The catch results showed that squid bait had the highest catch with 19 individuals, followed by scad bait with 13 individuals, and mackerel fish bait with the lowest catch at 9 individuals. The statistical analysis using one-way ANOVA (F-test) on the number of catch showed a significant difference. Further analysis using Tukey test showed a significant difference between squid bait and mackerel bait, while there was no significant difference between squid bait and scad bait, and also no significant difference between scad bait and mackerel bait. The length and weight of red snapper caught using a hand line with squid bait were dominated by larger size classes compared to the dominant size classes for mackerel bait and scad bait.